1992
DOI: 10.1002/bit.260391113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of initial events in bacterial surface colonization by two Pseudomonas species using image analysis

Abstract: The processes leading to bacterial colonization on solid-water interfaces are adsorption, desorption, growth, and erosion. These processes have been measured individually in situ in a flowing system in real time using image analysis. Four different substrata (copper, silicon, 316 stainless-steel and glass) and 2 different bacterial species (Pseudomonas aeruginosa and Pseudomonas fluorescens) were used in the experiments. The flow was laminar (Re = 1.4) and the shear stress was kept constant during all experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 21 publications
0
68
0
1
Order By: Relevance
“…After attachment of the colonizing bacteria, growth of the sessile population occurs. Although there is a reasonable amount of research done on all the steps in biofilm formation (66), a great deal of current interest resides in understanding the manner in which reversibly adhered bacteria make the transition to irreversible adhesion. Using GFP-labeled P. aeruginosa (76), the growth characteristics of planktonic bacteria and the initially adhering and secondary biofilm bacteria have been compared in a parallel plate flow chamber.…”
Section: Growth Of a Pseudomonas Aeruginosa Biofilm In A Flow Displacmentioning
confidence: 99%
“…After attachment of the colonizing bacteria, growth of the sessile population occurs. Although there is a reasonable amount of research done on all the steps in biofilm formation (66), a great deal of current interest resides in understanding the manner in which reversibly adhered bacteria make the transition to irreversible adhesion. Using GFP-labeled P. aeruginosa (76), the growth characteristics of planktonic bacteria and the initially adhering and secondary biofilm bacteria have been compared in a parallel plate flow chamber.…”
Section: Growth Of a Pseudomonas Aeruginosa Biofilm In A Flow Displacmentioning
confidence: 99%
“…This agrees with the results of Korber et al (17) where the same strains showed a two to three times enhanced attachment with motility. There are two common theories concerning the role of the flagella: (i) the ability to cross the energy barrier between the cell and the substratum to facilitate adhesion (22,34) and (ii) an effective increase in the cell diffusivity through the boundary layer fluid (24,28). It is possible that the lack of flagellar motion in the nonmotile strain (17) influenced the ability to cross the energy barrier, but it is more likely that the increased effective diffusivity of the motile strain resulted in more cell-surface collisions (23).…”
Section: Strain Comparisonsmentioning
confidence: 99%
“…The ability of a bacterium suspended in fluid to cross the boundary and diffusion layers and reach the surface is influenced by sedimentation, attractive interactive forces, and a velocity component toward the surface provided by collisions between flowing particles (38). Diffusion is a critical component of cell-surface interaction and can be influenced by cell motility which can act to increase the effective diffusivity of the cells to the surface by up to four orders of magnitude (24,25). Piette and Idziak (28) have shown that Pseudomonas fluorescens flagellated cells attached in greater numbers than deflagellated cells.…”
Section: Introductionmentioning
confidence: 99%
“…Muellar et al 1401 were able to determine rate coefficients for early bacterial colonization on copper, silicon, stainless steel and glass using a chemostat, a flow cell and a microscope equipped with an image analysis system. Reflective substrata were monitored using reflective light from a microscope equipped with a Nomarski lens and microscope output was linked to a video camera.…”
Section: Geesey Et Almentioning
confidence: 99%